Homocysteine is associated with plasma high-sensitivity cardiac troponin T levels in a community-dwelling population - Ye, Ping; Cao, Ruihua; Bai, Yongyi; Xu, Ruyi (Clinical interventions in aging, 2014)
Homocysteine (HCY) is associated with an increased risk for cardiovascular disease, possibly leading to myocardial damage. Cardiac troponin T (TnT), a marker of cardiomyocyte injury, can be detected by high-sensitivity TnT (hsTnT) assay. The current study investigated the relationship between plasma HCY and hsTnT levels in a community-based population. We related plasma levels of hsTnT to HCY levels in 1,497 participants (mean age, 62.4 years; 629 men, 868 women) from a community-based population in Beijing, People's Republic of China. In multiple logistic regression models, serum HCY was associated with a higher likelihood of detectable hsTnT (odds ratio 1.5; 95% confidence interval 1.07-2.10; P=0.018). A subsequent subgroup analysis found that in subjects aged 65 years and older, the association between hsTnT levels and HCY levels was strengthened. The association between hsTnT and HCY was not present in the younger subgroup (<65 years old). Levels of serum HCY are associated with hsTnT levels in the elderly, indicating a relationship between HCY and subclinical myocardial damage.